The Study of Community Interest in Gymnastics: Intrinsic and Extrinsic Factors: Studi Minat Masyarakat Terhadap Olahraga Senam: Faktor Intrinsik Dan Ekstrinsik - nancy trisari; Andy Supriady; Yasifa Wardiansyah (Journal of Physical and Outdoor Education, 2022)
This study aims to determine how much influence community interest in gymnastics in terms of intrinsic and extrinsic factors. This research is a quantitative descriptive research with a survey method approach using an interest questionnaire. The population of this study was the community in Ciwastra totaling 50 people, using total sampling technique, the sample of this study amounted to 50 people. The results of the research data analysis show that the interest factors that influence people's interest in exercising gymnastics with the percentage results are in the intrinsic category of 66% in the high category on health indicators.  In the extrinsic category of 54% in the low category, namely the family support indicator. Thus public interest in gymnastics is influenced by intrinsic factors on health indicators where Ciwastra people exercise gymnastics with the aim of maintaining health and fitness, while support from families on extrinsic factors is needed to support in achieving the goals of gymnastic sports activities. This study produced findings that Ciwastra society has a fairly good interest in a healthy lifestyle by doing gymnastic activities in order to maintain health and fitness.